If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + -4x = 2 + -1x Solving -10 + -4x = 2 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -10 + -4x + x = 2 + -1x + x Combine like terms: -4x + x = -3x -10 + -3x = 2 + -1x + x Combine like terms: -1x + x = 0 -10 + -3x = 2 + 0 -10 + -3x = 2 Add '10' to each side of the equation. -10 + 10 + -3x = 2 + 10 Combine like terms: -10 + 10 = 0 0 + -3x = 2 + 10 -3x = 2 + 10 Combine like terms: 2 + 10 = 12 -3x = 12 Divide each side by '-3'. x = -4 Simplifying x = -4
| 18/30=n/10 | | -10m+8=-122 | | 11x+3-3x=-4x-33 | | 3[x-4]=48 | | 6(x-2)/2=3(x+3)/6 | | 6+5x=8x-6 | | (-3x)+5=7 | | 10+2n=34 | | -6+14=x | | (2x/5)+(2x/3)=16 | | 1m+7=3+3m | | x-31=-24 | | x-88=-69 | | 3.6=6x | | 1/2(x+3/4)=x-13/8 | | 3p-6p=-7p+20 | | 2/3=14 | | n/30=5/6 | | 3x^2+8x=-13 | | 3x+26=6x+5 | | 14x-160=20x-10 | | (-37)+x=5 | | N-12n-24=101 | | 1m+9=12m-8m+21 | | 3x+26+6x+5=180 | | 4(y+5)+y=3(y+4)+6 | | x=1/2a*t^2 | | 52+x=65 | | 5/9x3/10 | | 24/1 | | 3x+26+6x+5=360 | | 4.3=x+3 |